Assessment of Modern Landscape Potential in the Caspian Coastal Plains - Nadirov, Magir Abdulali oghlu (Київський національний університет імені Тараса Шевченка, 2022)
Aim: In recent decades, high population growth rates have increased the impact on nature. The expansion of agricultural areas and the rapid appropriation of land require landscape assessment and systematic planning of nature management mechanisms. The main purpose of the study is to assess the natural landscape potential of the territory and propose measures that reflect the nature of the landscape and its regional and ecological significance. Methodology: The Caspian coastal plains of Azerbaijan, chosen as the study area, are distinguished by their sensitivity to anthropogenic impacts. In the evaluation process, the landscapes of the study area were categorized as weak, medium, and strong in terms of natural resource potential, productivity, and recreational potential. For determining the levels of sensitivity to technogenic impacts, landscapes were grouped according to the level of ecological tension into satisfactory, stressed, critical, and crisis levels and an expert assessment was carried out using a 100-point system. Results: According to the calculation, 54% of the coastal plains of the Caspian Sea that make up the study area are semi-arid landscapes, 14% are forests and meadows, 26% are dry steppes, and 5% are hydromorphic-intrazonal landscapes. During the assessment, it was revealed that landscapes with a low natural resource potential cover 42% of the area, landscapes with an average natural resource potential - 23%, and landscapes with a strong natural resource potential - 11%. Protected landscapes cover 24% of the study area. Evaluation of the sensitivity of landscapes to technogenic impacts showed that most of the territory (41%) is at a severe ecological level. Scientific novelty: The landscapes of the study area were evaluated in terms of natural resource potential and anthropogenic impacts. As a result, a system of measures for optimal management of landscape complexes was proposed taking into account the separated zones.
Keywords: natural landscape; ecological potential; coastal zone; ecological stress; optimization